2016
DOI: 10.14419/ijaes.v4i1.5899
|View full text |Cite
|
Sign up to set email alerts
|

Impact of gold prices on stock exchange market: a case of Karachi stock exchange market of Pakistan

Abstract: <p>The objective of the study is to examine the long-term relationship between gold prices and KSE-100 index of the Karachi stock market Pakistan. For the foreign and domestic capital investors, it is assumed that the gold is the safest heaven for making investment. On the other handstock markets are considered highly volatile. This study uses monthly data of two hundred forty eight months from October 1993 to May 2014. Time-series data of both variables Karachi Stock Exchange 100 index (KSE-100) and gol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…A ratio below 1 indicates that the bank is increasingly successful in creating value for shareholders and the amount of profit to shareholders will increase so that investors will be interested in investing their funds into the firm and thus the share price will increase. Thus this implies an inverse relationship with the dependent variable which is also supported by Arshad et al, (2015), Khan (2012) and Wadud (2017).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…A ratio below 1 indicates that the bank is increasingly successful in creating value for shareholders and the amount of profit to shareholders will increase so that investors will be interested in investing their funds into the firm and thus the share price will increase. Thus this implies an inverse relationship with the dependent variable which is also supported by Arshad et al, (2015), Khan (2012) and Wadud (2017).…”
Section: Discussionsupporting
confidence: 77%
“…However, some mutual elements were discovered, allowing the determinants of banking stock prices to be classified. Various studies on bankspecific factors and both micro and macroeconomic factors are listed below: Khan (2012) investigated the factors influencing share prices on the Karachi Stock Exchange. From 2000 to 2009, the study examined 34 KSE-listed companies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sahoo and Rajib (2012) evidently showed that the offering price-to-earnings ratio of an IPO influences its pricing. In addition, studies conducted by (Francis and Schipper 1999;Scott 2003;Ozlen 2014;Sahni and Mehandiratta 2013;Klein 1996;Purnanandam and Swaminathan 2004;Khan and Amanullah 2012;and Andriantomo and Yudianti 2013) have examined the relevance of accounting and financial data on IPO pricing and share prices. These studies established that there is a significant relationship between them.…”
Section: Literature Review and Rationale Of The Present Studymentioning
confidence: 99%
“…Several studies found that priceearnings ratio, book value per share, dividend per share, dividend yield, firm size, and leverage are the key predictors of the equity share price, (Srinivasan, 2012;Abdelkarim, 2014;Sanjeet, 2009). While others found that book value per share, dividend per share, dividend yield, and company size have no relationship with equity share price (Khan & Amanullah, 2012;Srinivasan, 2012;Yuga, 2014;Abdelkarim, 2014). Considering a fact that, directed toward stock market and we are also aware of ups and downs trend in stock market, so to safeguard the investors' investment on stocks, one cannot ignore…”
mentioning
confidence: 99%
“…External factors that affect stock prices are government regulations, business cycles, investor attitudes, market conditions, natural disasters, and contingencies such as strikes, closures, etc. (Khan & Amanullah, 2012). Numerous studies have been carried out on the determinants of equity share price, but there are some controversial findings on the factors influencing the equity share price.…”
mentioning
confidence: 99%